A simulation model to improve the value of rice supply chain (A case study in East Java – Indonesia). Issue 4 (4th July 2022) - Suryani, Erma; Hendrawan, Rully Agus; Muhandhis, Isnaini; Indraswari, Rarasmaya
ABSTRACT: This study aimed to improve the value of the rice supply chain through the use of a system dynamics (SD) model. SD was used since it is able to accommodate internal and external factors that influence the value of the rice supply chain. The simulation results showed that increasing the value of the rice supply chain can be achieved by increasing the quantity and quality of the crop yield and implementing the BioIndustry programme, farmer empowerment, and information sharing. This strategy is projected to increase rice productivity with an average of 1.4% per year. Increasing farmer profit can be achieved by empowering the farmers through the development of farmer groups and information sharing to cut the rice supply chain. Farmer's profit can also be increased by implementing the BioIndustry programme. By selling rice directly and implementing the BioIndustry programme, the total farmer profit will increase by 7.6% per year.